2017
DOI: 10.5617/adno.4334
|View full text |Cite
|
Sign up to set email alerts
|

Vilje, men manglende handlingskraft - skolelederes forståelse av tospråklige faglæreres plass i skolens læringsfellesskap

Abstract: Vilje, men manglende handlekraft -skolelederes forståelse av tospråklige faglaereres plass i skolens laeringsfellesskap

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…Studies on teaching English to immigrant students in Norway have shown that teachers are left on their own regarding effective English teaching strategies to support minority adult students (Surlakovic, 2014;Haukås, 2014). According to Spernes and Fjeld (2017), English teachers and other bilingual language teachers are less considered regarding planning of didactic work in schools. They concluded in their research that bilingual language teachers are not able to use their full potential due to little opportunity at their disposal to contribute to designing and planning of the English teaching curriculum, which in turn might have a negative effect on minority students' English learning (Spernes & Fjeld, 2017).…”
Section: Teacher Techniques For Teaching English As a Third Language ...mentioning
confidence: 99%
“…Studies on teaching English to immigrant students in Norway have shown that teachers are left on their own regarding effective English teaching strategies to support minority adult students (Surlakovic, 2014;Haukås, 2014). According to Spernes and Fjeld (2017), English teachers and other bilingual language teachers are less considered regarding planning of didactic work in schools. They concluded in their research that bilingual language teachers are not able to use their full potential due to little opportunity at their disposal to contribute to designing and planning of the English teaching curriculum, which in turn might have a negative effect on minority students' English learning (Spernes & Fjeld, 2017).…”
Section: Teacher Techniques For Teaching English As a Third Language ...mentioning
confidence: 99%